Effects of acute hypoxia on body substrate utilisation during progressively increasing work rate exercise tests - Özçelik, O?uz; Do?an, Halil; Keleştimur, Haluk (My University, 2003)
Respiratory quotient (RQ) was used to assess the effectiveness of exercise interventions in shifting substrate utilisation. The body's RQ can be estimated non-invasively from the ratio of CO2 production to O2 consumption. In the present study, we examined the effects of acute hypoxia on the substrate utilisation of the body and its non-invasive estimation from ventilatory and pulmonary gas exchange variables during exercise. Eight male subjects performed two progressively increasing work rate exercise tests (15 W/min) until the limit of tolerance: in one test they were breathing room air (normoxia) and in the other 12% O2 (hypoxia). Ventilatory and pulmonary gas exchange variables were measured using a turbine volume transducer and mass spectrometry and estimated breath-by-breath. During the warm-up period, RQ was found to be 0.79 ± 0.009 for normoxia, reflecting both carbohydrate and fat utilisation, and 0.94 ± 0.01 for hypoxia, reflecting predominant carbohydrate utilisation. At the metabolic transition point, RQ increased to 0.97 ± 0.04 in normoxia, reflecting predominantly carbohydrate utilisation. However, in the hypoxia study, RQ increased to 1.06 ± 0.01, reflecting not only predominant carbohydrate utilisation but also extra CO2 production and elimination. Consequently, substrate utilisation derives proportionally more from carbohydrate than from fat during exercise as the work rate increases. However, under conditions of acute hypoxia RQ estimation may not provide an accurate estimate of substrate utilisation.
Keywords: Exercise tests; Respiratory quotient; Substrate utilisation